Quality of local school wellness policies for physical activity and resultant implementation in Pennsylvania schools. (28th September 2017) - Francis, E; Hivner, E; Hoke, A; Ricci, T; Watach, A; Kraschnewski, J
Abstract: Background: In 2006, United States public schools participating in federal school meal programs were required to adopt school wellness policies. The effect of these policies on school nutrition environments is well documented; however, evaluation of physical activity policies has received less investigation. We aimed to evaluate how district wellness policies aligned to practice for physical activity implementation in 40 schools with high obesity rates (>24%). Methods: Wellness policies were evaluated using the validated Wellness School Assessment Tool (WellSAT). Concurrently, schools completed the validated Alliance for a Healthier Generation's Healthy Schools Program (HSP) self-assessment to evaluate physical activity practices. Overall, 13 of 20 physical activity measures from WellSAT and 12 of 13 physical activity measures from HSP were aligned to match policy with practice. Results: Most policy items scored 0 or 1, indicating either 'no mention in the policy' or 'containing weak or vague language'. Corresponding HSP results indicated that school physical activity practices are 'not in place' or 'under development'. A strong, positive, correlation ( r = 0.92, P < 0.001) indicated that a significant relationship exists between policy and implementation. Conclusions: Results indicate that most districts currently have weak policies regarding physical activity, limiting the potential to positively influence school-based physical activity.